Network analysis reveals microbe-mediated impacts of aeration on deep sediment layer microbial communities - Wang, Zhenyu; Liu, Feifei; Li, Enze; Yuan, Yongqiang; Yang, Yonggang; Xu, Meiying; Qiu, Rongliang (Frontiers in Microbiology, 2022)
Over-aeration is a common remediation strategy for black and odorous water bodies, in which oxygen is introduced as an electron acceptor of high redox potential and impacts aquatic microbial communities. In this study, black-odorous freshwater sediments were cultured for 9 weeks under aeration to investigate microbial covariations at different depths and timepoints. Based on community 16S rRNA gene sequencing, the microbial covariations were visualized using phylogenetic microbial ecological networks (pMENs). In the spatial scale, we identified simplified pMENs across all layers compared with anaerobic sediments, in terms of network size and connections. Aeration allowed sediment surface Desulfobulbaceae, known as cable bacteria, to reach the middle layer so that the middle layer had unique network characteristics, such as the most connectors, the least module hubs, a network hub, shorter average pathlength and predominantly positive covariations. A significant sulfate accumulation in the middle layer also indicated the most intense sulfide oxidation. In the time scale, similarly, aeration led to smaller pMEN sizes and higher portions of positive covariations. Therefore, we conclude that dissolved oxygen at the water-sediment interface may impact not only the surface sediment, but also the subsurface and/or deep sediment microbial communities mediated by microorganisms, particularly by Desulfobulbaceae.